METODE DAKWAH USTAD AMIRUDDIN DALAM PEMBINAAN PEMAHAMAN KEAGAMAAN PADA MAJELIS TAKLIM RIYADUL ULUM AS-SYAFI"™IYAH - Supardi, Supardi (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Majelis Ta'lim is a non-formal educational institution whose presence has a significant spiritual and social impact on forming religious character in society. The company of the Ta'lim Council in Banyu Urip village, Embung Tangar hamlet, West Praya sub-district, Central Lombok regency, aims to spread religious values or understanding to people who do not know understand religious teachings. The preachers' da'wah method has its characteristics that provide attractiveness to the congregation they foster. In this case, what Ustad Amiruddin did in conveying understanding, religion has a different style from other clerics, da'al, and preachers. This writing will try to show the communication methods used by Ustad Amiruddin in teaching the ta'lim assembly he supervises. With his unique technique and way. The article uses a descriptive analysis method with a qualitative approach. The primary data were obtained through interviews and observations of the studies provided by him and some of the worshipers who were part of his assembly. At the same time, the secondary is in the form of books that discuss da'wah methods, journals, and articles relevant to this study. Based on the research results that have been done, there are several conclusions obtained. With the da'wah communication approach, it can be seen that the communication methods of Da'wah Maradhah hasanah.